EVALUASI PROGRAM KELOMPOK KERJA GURU (MGMP) PENDIDIKAN AGAMA ISLAM TINGKAT SMP DI KOTA MASOHI KABUPATEN MALUKU TENGAH - St Jumaeda (al-Iltizam: Jurnal Pendidikan Agama Islam, 2020)
This research aims to determine the level of achievement of the activities of the MGMP subjects of Islamic religious education at junior high school level (SMP) in Masohi regency of Maluku Tengah. The study uses evaluative research methods on the MGMP activities of these PAI subjects using goal-oriented evaluation models developed by Ralph Winfred Tyler. Where the focus is on research into the level of goal achievement. Data collection In this study, conducted using observation techniques, interviews, questionnaires, and documentation. Subjects in the study were principals, PAI teachers, and MGMP-PAI administrators of Masohi. Results showed that the result of input evaluation related to MGMP-level capacity of Junior High School includes activity activities MGMP PAI has an average score, 85.78%, performance management MGMP PAI has an average score of 90.04%, facilities and infrastructure MGMP has an average score of 75.25%, KTSP availability in school member MGMP has a score of 92.75%. The implementation of learning has an average score of 88.02%, and the learning results assessment has an average score of 84.17%. Overall evaluation of inputs related to MGMP capacity of PAI at SMP level in Masohi is in good category. While for the output aspect related to the competency of teachers in school member MGMP, has an average value of 90.47% or the competency of the teacher is in good category.